2022
DOI: 10.3390/nu14214611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistant Dextrin on Intestinal Gas Homeostasis and Microbiota

Abstract: Previous studies have shown that a resistant dextrin soluble fibre has prebiotic properties with related health benefits on blood glucose management and satiety. Our aim was to demonstrate the effects of continuous administration of resistant dextrin on intestinal gas production, digestive sensations, and gut microbiota metabolism and composition. Healthy subjects (n = 20) were given resistant dextrin (14 g/d NUTRIOSE®, Roquette Frères, Lestrem, France) for four weeks. Outcomes were measured before, at the beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…At the taxonomic level, resistant dextrin increased the relative abundance of Fusicatenibacter ( P ≤ .05) and Blautia ( P > .05) among all donors ( Fig. 4C ), consistent with previous ex vivo and in vivo studies [ 14 , 68 , 69 ]. Human trials also identified a dextrin-specific increase of Parabacteroides [ 14 , 70 ], which was increased in our ex vivo cultures (2 3.5 -fold increase), though the effect was not significant.…”
Section: Resultssupporting
confidence: 90%
“…At the taxonomic level, resistant dextrin increased the relative abundance of Fusicatenibacter ( P ≤ .05) and Blautia ( P > .05) among all donors ( Fig. 4C ), consistent with previous ex vivo and in vivo studies [ 14 , 68 , 69 ]. Human trials also identified a dextrin-specific increase of Parabacteroides [ 14 , 70 ], which was increased in our ex vivo cultures (2 3.5 -fold increase), though the effect was not significant.…”
Section: Resultssupporting
confidence: 90%
“…Interestingly, the initial increase in gas production completely reverted upon continuous administration, reflecting a change in the fermentative pathways due to microbiota adaptation. The same phenomenon, initial fermentation and subsequent adaptation toward more efficient metabolic pathways, has been observed with other fibers with prebiotic properties ( 14 , 24 , 25 ). By contrast, poorly fermentable fibers, such as psyllium, do not induce detectable changes in intestinal gas evacuation, specifically the initial gas increase at initial administration ( 26 ).…”
Section: Discussionsupporting
confidence: 71%
“…These differences suggest that the origin of the sensations involves mechanisms related to gas, and other mechanisms possibly related to the bulk-forming effect of guar gum. Despite that guar gum did not influence fecal output, a potential effect on colonic biomass is plausible; indeed, other prebiotics produce a persistent increase in the volume of colonic biomass without changes in fecal output ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galactomannan is a natural plant polysaccharide mainly found in the endosperm of various plant seeds such as guar bean, locust bean, and cassia bean (Kian-Pour et al, 2023). It has been proved that galactomannan can withstand stomach and small intestine digestion to reach the lower digestive tract and is fermented by intestinal microbiota to produce beneficial bioactivators, which is a functional fibre (Xia et al, 2021;Barber et al, 2023). Guar gum is a type of galactomannan extracted from the endosperm of the guar bean, which is more widely cultivated and readily available, with a molecular weight of up to 2 9 10 6 Da (Tahmouzi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%